Development of methodology for assessing digital competence levels in personnel training - Avilkina, Svetlana V; Bakuleva, Marina A; Kleynosova, Nadezshda P (St. Petersburg State Polytechnical University Journal. Economics, 2019)
The developing digital economy alters the labor market demand both qualitatively and quantitatively, thus shaping a new paradigm for specialist training. In the RF regions professional education is meant to be significant in supplying economy with human resources. There must be competent trainers to enable trainees’ digital skills development. Research in determining levels of trainers’ digital literacy is one of the stages aimed at professional education improvement to procure digital economy with specialists. Issues of theoretical modelling of digital competences structure as well as methodological support of competences diagnosis are the key ones. This research is devoted to the development of methods for diagnosing levels of mastering digital competences in training. An overview of literature embracing such concepts as «digital literacy», «digital competences» is introduced. Basic features of currently available digital competences models are being described. Based on the investigations held by colleagues and with account of activities specifity of higher educational structures a new competence model including such major digital competences groups as «Digital office», «Net technologies use», «Digital security in professional activity», «Software and applications installation» has been developed. A description of the toolkit for diagnosing digital competence levels in training is given. Automatic data processing algorithm has been developed to enhance interpretation of digital competences levels. Diagnosis method to determine the level of digital competences proficiency was tried out in 2018 at the Ryazan Region Department of Education and youth policy. The research results may be used by public authorities in the decision-making procedures. Study materials may be applied in the process of further investigations of research and practice issues dealing with specialists training fit for digital economy. The toolset of field research including the method for trainers’ digital competences level testing may be replicated and used in both public administration and entrepreneurship activities.